The Epidemiology of Students Injuries in a Private Primary School in Turkey from 2012 to 2018 - GÜR, KAMER (MARMARA UNIV, INST HEALTH SCIENCES, 2020)
Objective: The aim of this study is to identify the occurrence frequency of school injuries, and to report where, when, and why they occur most. Methods: This retrospective descriptive study includes students aged between 6 and 11 years and is composed of 7042 school injury records. The school was chosen by the purposive sampling method since there was a school nurse working at school. The school injury records were formed by all injury records kept by the school nurse. The data were evaluated using descriptive statistics. Results: The study results showed that most of the school injuries occurred during the fall period (60.1%) and at break times (38.6%). As for the causes of the injuries, 13.3% of them were environmental, while 86.7% were behavioral. The floor on where most of the injuries occurred was rubber floor (53.6%) and the area where most of the injuries occurred was playground-garden (64%). The factor most frequently causing the injuries was hit collision, and the activity causing most of the injuries was running. The most frequently affected part of the body was head-neck-forehead-chin. The most common type of injury was tenderness and redness. Conclusion: With this study, it is seen that the rate of injury among students is high. Most of the school injuries occurred during the break times and mealtimes. Most of the causes of injuries were behavioral. These epidemiological data would be a guide for studies on prevention of injuries.
Keywords: Wounds and injuries; epidemiology; schools; nursing